Expression of sucrose metabolizing enzymes in different sugarcane varieties under progressive heat stress - Mehdi, Faisal; Liu, Xinlong; Riaz, Zunaira; Javed, Urooj; Aman, Afsheen; Galani, Saddia (Frontiers in Plant Science, 2023)
Studying the thermal stress effect on sucrose-metabolizing enzymes in sugarcane is of great importance for understanding acclimation to thermal stress. In this study, two varieties, S2003-US-633 and SPF-238, were grown at three different temperatures (±2°C): 30°C as a control, 45°C for various episodes of high temperature treatments and recovery conditions at 24, 48 and 72 hours. Data showed that reducing sugar content increased until the grand growth stage but sharply declined at the maturity stage in both cultivars.On the other hand, sucrose is enhanced only at the maturity stage. The expression of all invertase isozymes declined prominently; however, the expression of SPS was high at the maturity stage. Hence, the sucrose accumulation in mature cane was due to increased SPS activity while decreased invertase isozymes (vacuolar, cytoplasmic and cell wall) invertase activities at maturity stage in both cultivars. Heat shock decreased the sucrose metabolizing enzymes, sucrose content and sugar recovery rate in both cultivars. In contrast, heat-shock treatments induced maximum proline, MDA, H2O2 and EC in both cultivars. Notably, this is the first report of diverse invertase isozyme molecular weight proteins, such as those with 67, 134 and 160 kDa, produced under heat stress, suggesting that these enzymes have varied activities at different developmental stages. Overall, S2003-US-633 performs better than the cultivar SPF-238 under heat stress conditions at all development stages, with increased sucrose content, enzyme expression, proline and sugar recovery rate. This work will provide a new avenue regarding sugarcane molecular breeding programs with respect to thermal stress.